Chronic stress resulting from stressful life events and its role in the onset of primary Sjögren’s syndrome: a comparative analysis using the modified Holmes-Rahe stress scale - Marta Jaskólska; Iga Kościńska-Shukla; Dawid Jaskólski; Alessandro Viti; Marcin Ziętkiewicz; Michał Chmielewski (Stress)
Recent years brought considerable attention to the connection between chronic stress and the development of autoimmune diseases. However, little is still known about the impact of prolonged stress reactions on the onset and course of primary Sjögren Syndrome (pSS). This study aimed to seek for associations between chronic stress, resulting from stressful life events, and pSS. In the study, 50 patients with diagnosed pSS, as well as 50 control patients with osteoarthritis underwent an assessment. Modified Holmes-Rahe (H-R) stress scale was used in order to evaluate the impact of stressful events within 12 months prior to the diagnosis. Patients with pSS had a significantly higher total score on H-R stress scale within one-year preceding the disease diagnosis (152 ± 66.3 vs 50 ± 54.6; p [Formula: see text] 0.001). Additionally, the pSS patients more commonly than the controls reported a subjectively perceived correlation between stressful events and the occurrence of disease symptoms (50% vs 12%; p [Formula: see text] 0.001). Moreover, the H-R score at the time of the assessment correlated with the disease activity. The results support the view that pSS belongs to the group of diseases which pathogenesis is closely related to stressful life events. The novelty of this work lies in focus on both the correlation of stress on the onset of autoimmune disease as well as the activity of previously diagnosed disorder. Our data contributes to finding evidence-based medicine (EBM) arguments to what has until recently been merely a thematic observation—the harmfulness of negative stress on individual’s health status.